A companion to criminal justice, mental health and risk (Bristol: The Policy Press, 2014)
This unique and topical dictionary provides an array of expert analyses from key contributors in the field that explore the interface between criminal justice and mental health. Using concise yet robust definitions of key terms and concepts, it consolidates scholarly analysis of theory, policy and practice.
Includes bibliographical references and index.
Keywords: Mental health laws; Offenders with mental disabilities; People with mental disabilities and crime